2018
DOI: 10.1002/ejsp.2393
|View full text |Cite
|
Sign up to set email alerts
|

The influence of war on moral judgments about harm

Abstract: How does war influence moral judgments about harm? While the general rule is "thou shalt not kill," war appears to provide an exception to the moral prohibition on intentional harm. In three studies (n = 263, n = 557, n = 793), we quantify the difference in moral judgments across peace and war contexts, and explore two possible explanations for the difference. The findings demonstrate that third-party observers judge a trade-off of one life for five as more morally acceptable in war than in peace, especially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 57 publications
(110 reference statements)
3
33
1
Order By: Relevance
“…Another related, possible explanation for the discrepancy between our results and those of earlier work is that participants in the Benbaji et al study were imagining themselves as citizens of the same country as the soldiers and civilians; in the present study, participants were from a third, uninvolved country. Future studies could directly manipulate both the involvement of the participants’ (hypothetical) country and the participants’ role—as either observers or agents of the moral action—and thus further explore these possibilities (see also Watkins & Laham, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another related, possible explanation for the discrepancy between our results and those of earlier work is that participants in the Benbaji et al study were imagining themselves as citizens of the same country as the soldiers and civilians; in the present study, participants were from a third, uninvolved country. Future studies could directly manipulate both the involvement of the participants’ (hypothetical) country and the participants’ role—as either observers or agents of the moral action—and thus further explore these possibilities (see also Watkins & Laham, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moral psychology research provides a great deal of insight into the moral psychology of everyday life (Hofmann, Wisneski, Brandt, & Skitka, 2014), and has mapped out broad domains of moral value and basic principles of moral judgment grounded in religious texts (Graham, Haidt, & Nosek, 2009) and legal documents (Mikhail, 2007) from around the world. However, some researchers have also highlighted the context sensitivity of moral judgment (Carnes, Lickel, & Janoff-Bulman, 2015; Simpson, Laham, & Fiske, 2016) and in particular, the potential contrast between the morality of war and the morality of peace (e.g., Fiske & Rai, 2014; Giner-Sorolla, Leidner, & Castano, 2012; Watkins & Laham, 2018). In particular, Fiske and Rai (2014) suggest that the moral matrix of war is governed by a different set of relationships than is our everyday moral matrix.…”
Section: Discussionmentioning
confidence: 99%
“…And, they perceive soldiers as more dangerous, cold, and brave (Watkins & Laham, 2018). Further, they make divergent judgments of the same actions by soldiers on either side of a (just versus unjust) war (Watkins & Goodwin, 2019), and are more accepting of other people's parochial moral actions in war (Watkins & Laham, 2019). Since moral disengagement theory and similar lines of research focus on processes that are triggered by a (potential) conflict between actions and moral standards, they would have to explain whence this conflict is arising for these external, uninvolved, observers.…”
Section: The Conflict Approach: Interpreting War Through the Moralitymentioning
confidence: 99%
“…Moral judgments may, for example, depend on the relationships between the people involved in the scenario (e.g., family vs. strangers, Shaw, DeScioli, Barakzai, & Kurzban, 2017; Simpson, Laham, & Fiske, 2016) or the social context (e.g., intimates vs. task groups, Carnes, Lickel, & Janoff-Bulman, 2015). Watkins and Laham (2019) specifically compared moral judgments in war and peace contexts (using trolley problem scenarios) and found that people were overall more likely to accept a sacrifice of one life for many in war compared with in peace. Thus, although the use of a wide range of scenarios in the interest of generalizability might be justifiable or even desirable for some research programs, this approach will tend to obscure potential differences between war and everyday contexts.…”
Section: Alternative Approaches To Morality and Warmentioning
confidence: 99%
See 1 more Smart Citation